HUBUNGAN VOLUME KENDARAAN TERHADAP TINGKAT KEBISINGAN LALU LINTAS DI UNIVERSITAS NEGERI SEMARANG - Prahmani, Yonika Sindiana; Chasanah, Aisya Nurul; Maharani, Saffira Alyda; Hidayah, Harun Syamsudin Nur; Rabbani, Raka Restu; Fariz, Trida Ridho; Jabbar, Abdul; Deanova, Dendhie; Addini, Jihan Timur (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2023)
The research conducted on Jalan Taman Siswa No. 9 aims to determine the coherence between the number of two-wheeled and four-wheeled vehicles and the noise level on the highways around the campus. The data noise collection method uses a Sound Level Meter (SLM) with the HT-80A type and also counts the number of two-wheeled and four-wheeled vehicles passing by using the Traffic Counter application that has been installed in a smartphone. Noise can have an impact on human health, especially hearing problems and also cause inconvenience to both road users and residents in the vicinity. The variables that will be discussed are: volume of vehicles, especially two-wheeled and four-wheeled vehicles, and noise intensity. This data collection is needed to find the noise level and then compared using the standard allowable level, namely using the Decree of the State. Minister for the Environment No: Kepmen-48/MENLH/11/1996 for residential zones. Data analysis uses the Leq formula and then also uses the chi-square method to determine the relationship between the two variables. The total number of vehicles passing on the Taman Siswa road during the measurement was 23,530. In this study, the significance level used was 0.05 with the result that the p value for two-wheeled vehicles was 0.008 and for four-wheeled vehicles was 0.2. By obtaining the results of the calculation of a p value of 0.008, this shows that only two-wheeled vehicles are correlate with noise. whereas for four-wheeled vehicles with a p value of 0.2 does not show any correlation